Phytochemistry, medicinal chemistry & in-vitro cytotoxicity of ipomoea nil and gloriosa superba - Goel, Bharat (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Phytochemistry; medicinal chemistry; in-vitro cytotoxicity of ipomoea nil; gloriosa superba